Comparing performance indicators of obstetric and gynecology ward with expected limits of indicators - F Ebadi fard azar; A Choopani; H Saberi anari; N Mohammadi; SH Arkian; F Choopani (Tehran University of Medical Sciences, 2012)
Background: The existed difference statistical indicators is necessary to measure the efficiency of the health organization and as an exact strategy, could be removed the developed problems in heath services sectors. Materials and methods: This is a descriptive research as a cross sectional study throughout obstetric and gynecology wards in the general hospital of RASOOL. The questionnaires and statistical Forms applied for data gathering. The methods were completed questionnaires, statistical Forms, face to face interviews and observation. The Delphi technique, standardized questionnaires and references' text books used to determining the reliability and validity. Data analysis was done by using likret ranking. results: The results showed that some indicators, such as inpatient bed occupied rate (63%), bed turnover interval(5) & mean length of stay(4), patient per nurse(19), meanwhile service education(10),staff per active bed(1for 12), midwife per delivery bed(0), staff(50.9%) and patient satisfaction(89%) were lower than expected. Some indicators such as rooming in technique(100%), breast feeding(100%), patient information access from HIS system(100%), emergency and hostelling medicine access(100%), round and morning reports(100%), the mean admitted time in the ward(30 minutes), Infant and maternal mortality rate per total deliveries(0), and the percentage of trained patient(100%) were as expected. Some indicators such as expert physician per active bed (1 for 7) and C/S per total delivery ratio (69%) which was higher than expected, and the necessary data for calculating book & papers per assistant professor & non colonial infection rate were not found. Conclusion: Hospital indicators showed the performance of hospitals in the various bases. Therefore,the broad attentions to these indicators are necessary. Meanwhile, it should be compared them and to distinct time periods.